PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NON ASN MELALUI KEPUASAN KERJA DI KANTOR KECAMATAN KASEMEN KOTA SERANG - Wiwik Novianawati; Muhammad Suparmoko; Budi Ilham Maliki (MANAJEMEN, 2024)
This study aims to determine how transformational leadership and work environment influence employee performance through job satisfaction at the Kasemen District Office. The performance of an organization will be largely determined by the elements of its employees, therefore, when measuring the performance of an organization, it should be measured in terms of the work performance of the employees themselves. Good performance will be achieved if it is supported by the work abilities and organizational commitment of each employee The method used is a quantitative method with a descriptive Associative type. The population and sample used were 83 Non ASN employees at the Kasemen District Office. Associative research is a study that aims to determine the influence or relationship between two or more variables, where the process of taking samples from a population and using questionnaires as the main data collection tool. The data collection technique used a questionnaire to 83 (eighty-three) respondents with Likert scale measurements and using SPSS version 26. The results of the calculation of the direct effects of transformational leadership (X1), work environment (X2), job satisfaction (Z) on employee performance (Y). The results of the calculation of X1 against Y with a p-value of 0.018 <0.05. The results of the calculation of X2 against Y with a p-value of 0.000 <0.05. The results of the calculation of X1 against Z with a p-value of 0.000 <0.05. The result of X2 calculation against Z with p-values ​​0.041 > 0.05. The result of Z calculation against Y with p-values ​​0.149 > 0.05. Transformational leadership (X1) through job satisfaction (Z) on employee performance (Y) p-values ​​0.021 < 0.05 while the work environment (X2) through job satisfaction (Z) on employee performance (Y) p-values ​​0.032 < 0.05 In this study it can be concluded that there is a significant influence between transformational leadership, work environment through job satisfaction on employee performance.